Current Pathological and Laboratory Considerations in the Diagnosis of Disseminated Intravascular Coagulation - Cheng‐Hock Toh; Yasir Alhamdi; Simon T. Abrams (2016)
Systemically sustained thrombin generation in vivo is the hallmark of disseminated intravascular coagulation (DIC). Typically, this is in response to a progressing disease state that is associated with significant cellular injury. The etiology could be infectious or noninfectious, with the main pathophysiological mechanisms involving cross-activation among coagulation, innate immunity, and inflammatory responses. This leads to consumption of both pro- and anticoagulant factors as well as endothelial dysfunction and disrupted homeostasis at the blood vessel wall interface. In addition to the release of tissue plasminogen activator (tPA) and soluble thrombomodulin (sTM) following cellular activation and damage, respectively, there is the release of damage-associated molecular patterns (DAMPs) such as extracellular histones and cell-free DNA. Extracellular histones are increasingly recognized as significantly pathogenic in critical illnesses through direct cell toxicity, the promotion of thrombin generation, and the induction of neutrophil extracellular trap (NET) formation. Clinically, high circulating levels of histones and histone-DNA complexes are associated with multiorgan failure, DIC, and adverse patient outcomes. Their measurements as well as that of other DAMPs and molecular markers of thrombin generation are not yet applicable in the routine diagnostic laboratory. To provide a practical diagnostic tool for acute DIC, a composite scoring system using rapidly available coagulation tests is recommended by the International Society on Thrombosis and Haemostasis. Its usefulness and limitations are discussed alongside the advances and unanswered questions in DIC pathogenesis.